EVALUASI PROGRAM QUICK WINS DAN IMPLEMENTASI REKRUTMEN PENDONOR SEBAGAI UPAYA MENURUNKAN ANGKA KEMATIAN IBU (AKI) DI WILAYAH KERJA PUSKESMAS PAGUYANGAN KABUPATEN BREBES - Himatul Khoeroh (Siklus : Journal Research Midwifery Politeknik Tegal, 2022)
Quick Wins blood service program is a program to support nawacita in the health sector in order to reduce maternal mortality (MMR). Among them by increasing access to quality blood services which is carried out through collaboration between the Puskesmas, the Indonesian Red Cross (PMI) and the Hospital. This study aims to evaluate the Quick Wins program with elements of input, process and output with a qualitative design presented descriptively. Initial informants were determined by purposive sampling technique. The method of data collection was through in-depth interviews, observation and documentation of 4 initial informants consisting of coordinating midwives, health promotion workers, village midwives and cadres and 1 triangulation informant namely the head of the family health section of the Brebes district health office. The results of the study show that the input element has been maximized both from Human Resources (HR), funding or infrastructure. In the process element, the program has been implemented well, as evidenced by facilitating the adequacy of potential donors to replace the main donors whose families are pregnant women/Substitute Blood Donors (DDP). In terms of output, 50% of the Quick Wins program at the Paguyangan Health Center has made some village areas as foster villages, namely Taraban, Pagojengan, Ragatunjung, Kretek, Cilibur and Cipetung villages while the other 6 villages are still in the processKeywords : Quick Wins, donor recruitment, effort, AKI